Strain field reconstruction of crossbeam structure based on load–strain linear superposition method. (31st May 2021) - Cheng, Yangyang; Li, Zhaohua; Wang, Guangjun; Peng, Chang; Zhang, Lei; Yang, Wen; Jiang, Mingshun; Sui, Qingmei
Abstract: To address the problem that sensors cannot be affixed at certain critical locations of the crossbeam structure and the full-field strain distribution cannot be obtained in real-time. In this paper, a strain field reconstruction algorithm based on the load–strain linear superposition method is proposed to reconstruct the strain field distribution of the structure under arbitrary static load in three dimensions using the strain data at a limited number of discrete locations. Especially when the load is unknown, the reconstruction of the strain field is very meaningful. In the elastic range, the strain under multiple loads is the linear superposition of the strain under a single load. By establishing the finite element model, the strain field reconstruction effect of the crossbeam under double loads and three loads is analyzed. The average relative error is 2.8%, 1.6%, 2.2%, and 2.1%, which verifies the accuracy of the algorithm. On this basis, the feasibility of strain field reconstruction is verified in detail by a static load test. The experimental results show that there is a good consistency between them, indicating the effectiveness of the method. Even in the case of a single load, the strain field distribution of the crossbeam structure can be reconstructed in real-time by comparing the measured strain with the simulated strain.